Terms of Reference: CGIAR Science Group Evaluations - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2024)
The evaluation function of the Independent Advisory and Evaluation Services (IAES), is executing the 2024 evaluations of the three Science Groups (SGs)—Systems Transformation (ST), Resilient Agrifood Systems (RAFS), and Genetic Innovation (GI). The evaluation Terms of Reference (TORs), which are endorsed by the Strategic Impact, Monitoring, and Evaluation Committee (SIMEC) and build on the Concept Note, are presented to the CGIAR System Council (SC19) as a pre-read. The SG evaluations align with CGIAR's Evaluation Framework and Policy, and stem from the CGIAR 2030 Research and Innovation Strategy. Between 2022-23, the 2030 CGIAR Research Portfolio comprised of 33 Initiatives across three Action Areas (i.e., Science Groups).